The Fatty Acid Composition and Cyclopropene Fatty Acid Content of the Maturing Okra (Hibiscus esculentus L.) Fruits - Berry, Shiv K. (1980)
Okra (Hibiscus esculentus, L.) fruits are consumed as vegetable throughout the world. The fatty acid composition of the fruits harvested on the 5th, 6th, 8th and 12th day after flowering was determined by gas liquid chromatography. As the fruits matured, C16:0 fatty acid content increased with a corresponding sharp decrease in C18:3 fatty acid concentration. The lipids in immature fruits contained C24:0 fatty acid, whereas the oil recovered from fully matured seeds had C21 :5 fatty acid instead. Cyclopropene fatty acids were not detected in the lipids of immature fruits, occurring only in small amounts in the oil of fully matured seeds.